Penilaian Status Gizi, Edukasi dan Pengenalan Inovasi Pangan sebagai Upaya Pencegahan Stunting pada Ibu Hamil di Desa Rejosari Kabupaten Demak - Fina Dwi Aryanti; Nikmatul Luailiya; Nana Misrochah; Nur Kiki Patmawati; Eka Bima Christiana; Muslimah Hasanah (Jurnal Pengabdian KOLABORATIF, 2024)
Stunting is malnutrition that occurs gradually and is prolonged. In general, according to Riskesdas (2018), the prevalence of stunting in Indonesia is 30.8%, and in Demak 26.1%. Meanwhile in Rejosari Village. Based on data from local midwives, there are 15 stunted children in Karangawen, Demak. The purpose of dedication is as a preventive measure so that the incidence of stunting under five in Rejosari Village, Demak Regency does not increase. The implementation began with a health stand, and interactive discussions, and ended with a cooking demonstration for pregnant women. The activity began with an anthropometry stand, continued with education on the importance of the role of 1000 HPK, questions, and answers, and ended with a demonstration on making Moringa Chicken Tofu Balls. The results of the "Si Penting" program show that there are still pregnant women who have the potential to give birth to LBW children, as evidenced by a BMI before pregnancy of less than 18 kg/m2 and a LILA of less than 23.5 cm. Apart from that, food education and innovation activities ran smoothly, participants asked many questions and had lively discussions.